The impact of the use of some chemical fertilizers on some physiological and genetic traits and some active substances to assess the celery plant (Apium graveolens L.) - Ibrahim Omar Saeed (Tikrit Journal of Pure Science)
Experiment conducted Alsnaddein capacity (5 kg) in the agricultural season in 2013 on the local plant celery Apium graveolens L. To determine the efficiency of the use of different levels of fertilizer nitrogen, phosphorus and their interaction on the physiological and genetic traits active substances to plant celery, and use the design of global experience Factorial Experiment using three levels of nitrogen in the form of urea  (NH2) CO  (N% 46 and three levels of phosphorus in the form of fertilizer Super triple calcium phosphate Ca (H2PO4) 2 (P2O4% 45) and three levels of nitrogen and phosphorus in the form of mixed fertilizer, said results of the study as follows :